Croatian disaster risk management legislation gap analysis - Šimac, Zaviša; Holcinger, Nataša (Crisis Management Days, 2024)
Damages caused by disasters have already become a global, regional, and local governance problem that lacks effective legislative frameworks (Manyena et al., 2013). Despite numerous disastrous events and mounting natural hazard event damage and losses (MinFin, 2024), activities between events and lack of strategic planning in the last ten years, disaster risk management and disaster risk reduction are far from getting the needed resources, acceptance and understanding in Croatia. National policies and legislation on disaster risk reduction are vital for shaping efficient disaster risk management implementation (Bang, 2021). Disaster risk management legislation is the foremost instrument to shift focus from unsustainable disaster response towards risk reduction. The Sendai Framework for Disaster Risk Reduction 2015-2030, with its seven targets and four priorities, is a global outline for implementing disaster risk reduction measures to save lives, livelihoods, health, and assets (UNDRR, 2015). This research analyses current Croatian disaster risk management legislation and policy against the Sendai Framework for Disaster Risk Reduction 2015 -2030 (UNDRR, 2015) recommendations. The research aims to identify legislative gaps and necessary improvements. Qualitative research assessed Croatian’s ability to mitigate, assess, respond to, and recover from disasters caused by earthquakes, forest fires, floods, and landslides, the four unacceptable national disaster risks according to the National Disaster Risk Assessment. Croatia aims to align its disaster risk management policies with international commitments. Notably, it adheres to the 2015-2030 Sendai Framework for Disaster Risk Reduction (UNDRR, 2015) and the Sustainable Development Goals of the 2030 Agenda for Sustainable Development (SDG, 2015). The Republic of Croatia has established a robust national emergency management system. Under this system, the government oversees the civil response activities, with the Civil Protection Headquarters coordination and support from the operational forces defined by the Act on Civil Protection System, emphasising firefighters, the Croatian Mountain Rescue Service, and the Croatian Red Cross Croatia. With an already established emergency management system, Croatia reportedly recognises the importance of shifting from a reactive to a proactive disaster risk management approach. Consequently, the Croatian Disaster Risk Reduction Platform was established to achieve an integrated DRR policy. While most initiatives originate at the national level, sectoral strategies, legislation, and activities need better alignment. Several legislative pieces define sector-specific DRR measures, including the Water Act (HV, 2019), which addresses water-related risk management. The Civil Protection System Act (MUP, 2015) partially defines disaster risk management planning, focusing primarily on response—the Forest Fire Protection Ordinance (HŠ, 2014), which focuses on forest fire prevention. However, more substantial implementation of the National Disaster Risk Management Strategy (MUP, 2022) aims to mitigate the gaps in the current legislation. Although the Strategy should consolidate the existing sectoral approaches and outline a unified framework for risk reduction, the absence of an overarching legislation framework such as a Disaster Risk Reduction Act poses a significant obstacle to implementing all recommendations laid down by the Sendai Framework for Disaster Risk Reduction. Priority 1: Understanding disaster risk implementation into national legislation needs significant political will and a push towards mainstreaming planning based on an understanding of disaster risk in all its dimensions of hazard characteristics, vulnerability, capacity, and exposure of people and property. Although Croatia has a National Disaster Risk Reduction Platform, there is still a significant gap in sectorial coordination, defining roles and responsibilities, coherent policies, and incentives for implementing public and private sectors’ DRR measures. The reason lies in a nonexistent DRR legislative that would institutionalise all National Platform and Platform members’ obligations. The existing National DRR Platform was established by the Croatian Government’s decision, which only loosely defined the Platform’s members’ mandates. Moreover, the Homeland Security Act (MORH, 2017 )creates an overlap in coordination. Members of the National DRR Platform and the Civil Protection Headquarters overlap extensively with the Homeland Security Council (political level) and Homeland Security Coordination (operational level), both of which were established by the Homeland Security Act. The Homeland Security Act does not intervene in the competencies of the Homeland Security system members as defined by their legislative and by-laws. The Homeland Security Act defines when and under what conditions a state of emergency is declared, but it fails to define the members’ roles within the system. The former is defined by The Civil Protection System Act (MUP, 2015) and The Act on the Mitigation and Elimination of the Consequences due to Natural Hazards(MinFin, 2019), while the latter still requires further improvement. The current state makes Priority 2: Strengthening disaster risk governance to manage disaster risk only partially implemented. And in a majorly confusing manner. Croatian authorities have yet to gain and implement knowledge of the importance of investing in disaster risk reduction for resilience, as outlined by Priority 3. implementing and investing in structural and non-structural measures is pivotal in securing resilient local government and can lead to the growth and sustainable development of local communities and, consequently, a resilient Republic of Croatia. Nevertheless, some steps are taken in a positive direction, such as risk transfer in agriculture. The national government offers incentives on insurance policies, which can lead to public and private sector investments in disaster risk reduction measures. Croatian disaster preparedness is defined in detail with civil protection plans on all three levels of government, national, regional and local, operational forces plans, and civil protection plans of legal persons of civil protection interests defined by the Act on Civil Protection System and sectorial standard operating plans. However, the legislation has yet to define recovery, rehabilitation, and reconstruction plans and the opportunity to «Build Back Better» by integrating disaster risk reduction measures. New legislative pieces were developed each time for the 2014 Slavonia flood and recent earthquakes in Zagreb and Petrinja, making recovery somewhat ineffective and showing the importance of implementing Priority 4. of the Sendai Framework for Disaster Risk Reduction. An analysis of Croatia’s disaster risk management legislation and policy suggests four areas of interest for improvement. Improvement in the Croatian disaster risk reduction system should be focused on (1) battling political disinterest and improving engagement, (2) decision-making authorities, (3) capacity building, and (4) improving risk assessment, developing relevant data with objective and uniform disaster database, both sectorial and local. The conclusion is that while the wording has changed, the disaster risk legislation and practice have not significantly shifted from responding to natural hazard events to reducing vulnerability and increasing resilience. Shifting the focus to dealing with vulnerability and resilience is only possible if overarching disaster risk management legislation is developed and one sole coordinating authority is established, independent of sectorial/hazard-competent organisations and response authorities.